Influence of Agricultural Extension Services for A Sustainable Sugarcane Production in the Philippines - Oñal, Jr., Paulino A.; Baldonebro, Jessel Jane G.; Andrade, Francis E. (Future Science / FSH-PH Publications, 2025)
Agricultural extension is an essential strength in agricultural development and social innovation factor. It is a key that can capacitate sugarcane farmers to accelerate the adoption of technology in farm production. Furthermore, agricultural extension services are instrumental in bridging the gap between agricultural research and practical farming. This study aims to determine the influence of extension services on the production of sugarcane in the Philippines. Descriptive method of research was employed in the study. The respondents were 320 sugarcane farmers that were randomly identified from seven locations in the Visayas. The instrument used was the validated survey questionnaire used by Oñal, et al (2021). Results show that there is a significant difference in the production of sugarcane among location with a mean of 2.28 or an average of 50-64 TC/ha (ɑ=0.05). The advocacy on planting of high yielding varieties (HYVs) that are adaptable to sugarcane farms (m=3.87, ɑ=0.05) and the dissemination of different projects to the farmers (m=3.98, ɑ=0.05) had a significant impact on sugarcane production at >65 Tons/ha. Furthermore, the two agricultural extension services mentioned are moderately correlated with the production. The study recommends that the advocacy for planting of HYVs suitable to farms should be further prioritize including the strong dissemination of various agricultural development to bolster the sugarcane production in the area.